Alternative fixed income indexation: A study on fundamental indexes in the South African corporate bond market - Kujenga, Tinodiwanashe (Department of Finance and Tax, 2015)
Indexation serves as a cornerstone of the asset management field. As such, asset managers across the globe are constantly testing different methodologies to find one which provides consistent superior performance against the rest. While previously, market capitalization weighted indexes have been the popular and simpler method to implement, the search of outperformance has evolved from only focusing on picking securities from larger institutions and has expanded to trying out various weighting methods so as to maximize on the best performing instruments. As yet, there is no definite winner, with the success of most methods being largely influenced by the type of market for which the index is intended as well as the macro-economic environment prevailing during the period. However, the fundamental indexation method has recently gained popularity, particularly in the global equity markets. This research paper explores the method of fundamental indexation and applies it to the corporate fixed income section of the South African market. The main aim is to determine whether the significant outperformance, which has been found in global fixed income markets as well as global and domestic equity markets, will hold true when the method is implemented on domestic bonds. This investigation uses the current domestic market corporate bond index, the OTHI, as a benchmark against two alternative bond indexes created using the fundamental indexing methodology. The first alternative index is a direct replication of the OTHI and has identical constituents to those of the original. This is called the OTHI_ALT. However, finding that the OTHI is heavily influenced by the debt issues of the government and other parastatal companies, a second more diverse index is created. This is named the SAFI_ALT, which maintains the same number of constituents in each period as the OTHI, but uses different universe selection methods and thus has different constituents. The study creates four sub-indexes for both the OTHI_ALT and the SAFI_ALT, using the fundamental metrics of the companies whose securities are included in the index. The fundamentals used are Sales, Cash Flow and Book Value, and in addition a Composite of all three fundamentals.